Translation-Invariant Bipolarons and Charge Density Waves in High-Temperature Superconductors - Lakhno, Victor D. (Frontiers in Physics, 2021)
A correlation is established between the theories of superconductivity based on the concept of charge density waves (CDW) and the translation invariant (TI) bipolaron theory. It is shown that CDW are originated from TI-bipolaron states in the pseudogap phase due to Kohn anomaly and form a pair density wave (PDW) for wave vectors corresponding to nesting. Emerging in the pseudogap phase, CDW coexist with superconductivity at temperatures below that of superconducting transition while their wave amplitudes decrease as a Bose condensate is formed from TI-bipolarons, vanishing at zero temperature.